Key Considerations for High Current Fuel Cell Catalyst Testing in an Electrochemical Half-Cell. Issue 4 (9th February 2017) - Pinaud, Blaise A.; Bonakdarpour, Arman; Daniel, Lius; Sharman, Jonathan; Wilkinson, David P.
Abstract : An economical and novel half-cell approach for quick and precise measurement of oxygen reduction catalysts in various practical electrode formats, including GDE and bonded GDE/membrane layers is demonstrated. Fuel cell current densities (∼1 A/cm 2 ) were achieved with the key design considerations clearly outlined, to highlight the challenges in developing such a test platform. Constant current polarizations with IR drop measurement at each step are found to provide a simple, reproducible method of measuring catalyst performance. An optimal electrolyte concentration of 1.0 M HClO4 balances the requirement of non-limiting H + transport at high currents whilst minimizing the effect of electrolyte impurities, which reduce Pt activity. The half-cell used here can accurately provide the ORR activity of commercial products showing good agreement with measurements made in fuel cell hardware, but at a significantly lower testing cost. This half-cell approach can be used to characterize various types of GDEs and CCMs with different catalyst layers.